The Effects of Vitamin C for Iron Supplementation during Pregnancy with Risk of Anemia: A Randomized Controlled Clinical Trial - Srimaneesiri, Lalitpan; Puttanavijarn, Lunthaporn (Thai Journal of Obstetrics and Gynaecology, 2025)
Objectives: To evaluate the effects of combining vitamin C with iron supplementation on hemoglobin (Hb) and hematocrit (Hct) levels among pregnant women at high risk of anemia. Materials and Methods: A randomized controlled trial was conducted among singleton pregnant women at 14-28 weeks of gestation, with Hb ≥ 10.5 g/dL, Hct ≥ 32% and ferritin ≥ 30 ng/mL, who were at risk of anemia (> prior 2 pregnancies, age < 18 or > 35 year-old or body mass index < 18 kg/m2 ). Women attending Rajavithi Hospital from July 2023 - June 2024 were randomly assigned to receive vitamin C (500 mg) plus iron supplement or iron only. Hb and Hct were measured 2 months after intervention. Results: Total of 100 enrolled participants, 22 (22%) were excluded for having ferritin levels < 30 ng/mL. The remaining 78 women were randomized, with 38 in the experimental group (vitamin C plus iron) and 40 in the control group (iron only). There were no significant differences in Hb and Hct levels between the two groups, both initially and 2 months after the intervention (Hb: mean difference (MD) -0.11; 95% CI -0.53, 0.31; p = 0.609 and MD -0.24; 95% CI -0.67, 0.32; p = 0.253; respectively) (Hct: MD -0.77; 95% CI -1.96, 0.55; p = 0.266; MD -0.70; 95% CI -1.97, 0.58; p = 0.282). The repeated measure analysis of variance (ANOVA) showed non-significant overall mean differences. No adverse events were reported. Conclusion: Vitamin C was not essential with iron supplements to improve Hb and Hct levels in pregnant women at risk of anemia.